THE PORTRAYAL OF MAIN WOMAN CHARACTERS BASED ON CONFLICT REVEALED IN JANE FALLON'S NOVEL GETTING RID OF MATTHEW : A Descriptive Study Using Existentialist Feminism Analysis - Sinta Dein Wulandari, - (2011)
The research paper analyzes the portrayal of main woman characters based on conflict revealed in the novel Getting Rid of Matthew written by Jane Fallon. The aim of the study is to find out (1) How does the author portray the main woman characters based on conflict on the novel? (2) What conflicts are experienced by the main woman characters? (3) How the portrayal is seen in the Existentialist Feminism point of view?" The study uses a qualitative descriptive approach to answer the formulated research questions above. This Research employs close reading strategy in which the novel is read thoroughly and carefully to determine the main issue of the study and to collect data. Afterwards, the data collected in the form of textual evidences is analyzed by means of existentialist feminism proposed by Simone De Beauvoir. The research found that the author uses telling and showing methods in portraying the main woman characters, they are portrayed both feminine and masculine characteristics. In terms of conflict, the woman characters experienced both internal and external conflict in portraying their role as a woman. Meanwhile, in the view of existentialist feminism, the main woman characters are portrayed as the other who identifies their existence in regard to man, yet going to work and being intellectual become their power to liberate themselves as a woman.